Analisis Resiko Keterlambatan Pembayaran Pinjaman Anggota Terhadap Stabilitas Keuangan Pada Ksp Cu Bahtera Sejahtera - Radja Tuka, Moses; Maria Dilliana, Siktania; Grasella Tunya, Maria (Jurnal Projemen UNIPA, 2026)
Delayed loan repayment by members is one of the main risks that can affect the financial stability of savings and loan cooperatives. This study aims to analyze the risk of delayed loan repayment by members and its implications for financial stability at KSP CU Bahtera Sejahtera. The study employed a descriptive qualitative approach with data collected through observation, interviews, and documentation. The data consisted of primary data obtained from cooperative management and staff, as well as secondary data in the form of financial reports and non-performing loan data for the period 2022–2024. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings indicate that delayed loan repayment is influenced by members’ repayment capacity, weaknesses in credit monitoring, and unstable economic conditions of members. These conditions have an impact on cash flow, liquidity, and the overall financial health of the cooperative. The study highlights the importance of applying prudential principles in credit provision, strengthening credit monitoring systems, and utilizing non-performing loan data as a basis for risk management to maintain sustainable financial stability